Can contract farming increase farmers’ income and enhance adoption of food safety practices? Evidence from remote areas of Nepal - Kumar, Anjani; Roy, Devesh; Trapathi, Gaurav; Joshi, Pramod Kumar; Adhikari, Rajendra Prasad (International Food Policy Research Institute, 2016)
Growing inequality has become an important concern in many countries. One of the ways that inequality is perpetuated is through differential market access across regions. This research deals with one of the primary determinants of regional inequality manifested in terms of market access. Nepal is one country where hierarchical geography leads to regional inequality. Differential market access can cause as well as accentuate inequality among farmers. Coordination arrangements such as contract farming can improve outcomes for the farmers and integrators on the one hand, but on the other hand it can accentuate inequality if only some regions benefit from it. With this background, in this paper we study the case of contract farming for exports with farmers in remote hilly areas of Nepal. The prospect for contract farming in such areas with accessibility issues owing to underdeveloped markets and lack of amenities is ambiguous. On the one hand, contractors in these areas find it difficult to build links, particularly when final consumers have quality and safety requirements. On the other hand, remoteness can make the contracts more sustainable if the agroecology offers product-specific quality advantages and, more important, if there is a lack of side-selling opportunities. At the same time, concerns remain about buyers’ monopsonistic powers when remotely located small farmers do not have outside options. This study hence quantifies the benefits of contract farming on remotely located farmers’ income and compliance with food safety measures. Results show that contract farming is significantly more profitable (offering a 58 percent greater net income) than independent production, the main pathway being higher price realization, along with training on practices and provision of quality seeds.